DAKWAH AHLULBAIT KAJIAN KANG JALAL - BUKHARI BUKHARI (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
This article is based on the basic assumption that da'wah is a dynamic activity. Da'wah activity organized by Dakwah Ahlulbait Kajian Kang Jala/ (KKJ/The Kang Jalal Circle), under the institution of Ikatan Jamaah Ahlulbait Indonesia (IJABI/The Indonesian Ahlulbait Society) is one of dynamic da'wah in facing the social change. The main conclusion of this article is that the Da'wah Ahlulbait of the KKJ provides the participants intellectual enlightenment by using critical, rational and historical approaches with persuasive and empathic communications. Moreover, sufistic and taqiyyah approaches are specially used for spiritual enlightenment. The Da'wah Ahlulbait of the KKJ focuses much on the Shi'ite view and the psychological therapy in which Kang Jalal himselff unctions as a single player. Keywords: Dakwah, Ahllulbait, Kang Jalal Study